Peran Kontrol Sosial Terhadap Perilaku Kenakalan Siswa Di Sekolah - Satyagraha, Richardo Kurnia; , Dr. Eny Purwandari, M.Si (2016)
Social control is useful in schools to prevent juveniles delinquency in the school environment, for their social control is expected to align delinquency committed by students. Juveniles deliquency constitute misbehaviors that contradict the norm regulation of schools. This study aims to know and understand the role of social control, there are elements of attachment, commitment, involvement and belief of the behavior of student misbehavior. The method of data collection in this study is using an open questionnaire. The informants in this study included 233 students of vocational school level. The results showed that low or weak commitment make up the so-called violation of delinquency. Form of delinquencies occur because there is an attachment with a figure friends with high-intensity interaction in school. Viewed from the side of the students involvement in extracurricular activities and the will to admonish the students who violate school rules. Those correlated the belief that with students who think that rules are made by the school is good and for the good work, in terms of belief are only limited knowledge of it.